menu search
brightness_auto
more_vert

i. 7x + 3y = 15; 12y - 5x = 39

ii. \({x+y-8\over 2}={x+2y-14\over3}={ 3x-y\over4}\)

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike

1 Answer

more_vert
 
verified
Best answer

Solving the folllowing equation with crammers method or rule

solution of 1

Given:

7x+3y=15  ....(1)

12y-5x=39 ........(2)

Equation (1) and (2) are in ax+by=c form 

comparing the equations with standard form 

a1x+b1y=c1 and a2x+b2y=c2

we get ,

a1 = 7, b1 = 3, c1 = 15 and

a2 = -5, b2 = 12, c2 = 39

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike

Related questions

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 501 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer

5.2k questions

4.7k answers

75 comments

393 users

...